Compact Lowpass Filter with Ultra-High Figure-of-Merit and Flat Group Delay. Issue 6 (2nd November 2018) - Hayati, Mohsen; Ekhteraei, Milad; Shama, Farzin; Sherafat Vaziri, Hamid
ABSTRACT: This paper presents a microstrip lowpass filter with compact size, and ultra-wide stopband. The structure consists of a modified hairpin resonator loaded with tapered cells and the circular patches as the suppressing cell. The proposed lowpass filter has −3 dB cut-off frequency at 1.64 GHz. It also has suitable performances such as: ultra-sharp transition-band of 0.09 GHz that is from −3 to −20 dB, an extended stopband bandwidth from 1.73 to 21 GHz with the attenuation level more than −20 dB, low insertion-loss, flat group delay in the passband, and simple structure. The proposed lowpass filter is simulated and fabricated and there is good agreement between the simulation and measurement results.